(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, it is described that during the process of forming the physical culture among teenagers, young athletes master movements and related knowledge, develop their physical abilities and physical qualities. The article also describes psychological, physiological and morphological characteristics of young athletes.